Temporal demography of lesser scaup: a species in decline - Navarre, Kelsey, author; Koons, David, advisor; Kanno, Yoichiro, committee member; Aldridge, Cameron, committee member (Colorado State University. Libraries, 2020)
A central goal of wildlife management and conservation is to determine which demographic parameters have the greatest influence on population growth rate to focus management actions for species of concern. Understanding how environmental conditions influence intra- and interannual variation in demographic parameters, and in turn population growth rates, requires long-term studies. This allows researchers to account for temporal covariation in demographic parameters that may have a greater influence on population dynamics than direct variation in the demographic parameter. One such species that could benefit from a better understanding of temporal variation and covariation in demographic parameters is lesser scaup (Aythya affinis, hereafter scaup), which has declined continentally since the early 1980's. I contributed to and utilized a long-term study of scaup demography at Red Rock Lakes National Wildlife Refuge in southwestern Montana, USA to 1) explore how environmental conditions influenced intra- and inter- annual variation in clutch size and nest survival, and 2) incorporate temporal (co)variation in demographic parameters into population models to decouple the influence of parameter variation, versus covariation, on population growth rate. To address my first objective, I considered an array of environmental covariates that were hypothesized to influence inter-annual variation in clutch size and nest survival such as water levels, water level phenology, and water temperature. In addition, I considered intra-annual covariates that could influence these vital rates, such as nest initiation date and day of the breeding season, which could serve as proxies for seasonal changes in resources, predators, or both. Clutch size varied much more within years across nest initiation dates (3.18-10.05), than it did across years (7.51 – 8.38). Given the constrained range of clutch sizes across years, none of the environmental covariates exhibited significant relationships with clutch size. In contrast, nest survival varied little intra-annually (e.g. 2018 nest survival 0.38 ± 0.03), but greatly interannually (0.27 – 0.58). Water level phenology did influence nest survival, such that years when maximum lake levels were reached late in the breeding season relative to mean nest initiation date, had the highest nest survival rates. To address my second objective, I incorporated results from my first chapter along with annual estimates of female breeding propensity, duckling survival, first-winter survival of females, adult female seasonal survival, process variance of each vital rate, and correlation between each pair of vital rates into a time-variant population model and conducted a prospective and retrospective perturbation analysis of population growth rates. The population model revealed that the study population is declining by approximately 6% each year. Results from the prospective perturbation analysis indicated that breeding season and non-breeding season adult survival had the highest stochastic elasticities (0.84 and 0.82 respectively), and thus had the greatest potential to influence the stochastic population growth rate. Whereas, retrospective analyses indicated that fluctuations in duckling survival made the largest contribution to realized population growth rates in the past (64%). Additionally, covariation in demographic rates explained 37% of variation in realized growth rates compared to 63% being attributable to direct temporal variation in the vital rates. These findings collectively suggest efforts to manage water phenology at Red Rock Lakes National Wildlife Refuge could positively influence nest survival and efforts should focus on finding ways to increase duckling survival to have the greatest impact on population growth rate. More broadly, covariation in demographic rates can explain a large proportion of variation in population growth rate and should be incorporated into population models of declining species to more accurately determine points in the life cycle that truly drive population dynamics, and therefore provide sound information to managers aiming to conserve the species.
Keywords: nesting ecology; temporal covariation; vital rates; perturbation analysis; Aythya affinis